Dengue fever in pediatric travelers – a literature review - Ziopaja, Zuzanna; Kryś, Kinga; Owczarczak, Weronika; Małecka, Lena; Gowin, Ewelina (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Dengue fever, predominantly affecting children, is/has been becoming increasingly relevant as cases rise globally due to climate change and expanded travel to endemic regions. In Poland, reported dengue cases rose from 70 in 2023 to 126 in 2024, indicating a growing risk even in temperate zones. Most infections are mild; however, severe cases are notably more common in children and those with comorbidities. The dengue virus has four serotypes, and reinfection can lead to more severe disease. Currently, two vaccines, Dengvaxia and QDENGA, provide options for prevention, with QDENGA showing promise for use regardless of prior infection status. A review of literature from 2009–2024 highlighted 95 pediatric cases of dengue linked to travel in/to endemic regions, emphasizing the need for increased awareness and preventive measures, particularly among families traveling to areas with known dengue transmission. Continued vigilance and education in travel medicine are essential to mitigate risk.